2019
DOI: 10.1136/bmjopen-2019-029529
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of depressive symptoms in 4 years of follow-up among mid-aged and elderly community-dwelling Chinese adults: findings from the China Health and Retirement Longitudinal Study

Abstract: ObjectivesThe purpose of this study was to examine the incidence of depressive symptoms, and determine if baseline risk factors conferred a risk for incident depressive symptoms in nationally representative sample of mid-aged and elderly Chinese adults.DesignThis study was a secondary analysis of a prospective cohort from a nationally representative sample.SettingCommunity samples were recruited from the baseline survey of the China Health and Retirement Longitudinal Study. A four-stage, stratified, cluster pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 57 publications
6
26
3
Order By: Relevance
“…Our findings suggested Depressive symptoms among the Chinese elderly 163 that short sleep duration was associated with high rates of depressive symptoms. This result was consistent with the results of Wen et al (2019), who found that elderly people with long sleep duration at night have a lower risk of developing depressive symptoms than those with short sleep duration. Sleep and depressive symptoms have a multifaceted interplay between them.…”
Section: Sleep Durationsupporting
confidence: 93%
“…Our findings suggested Depressive symptoms among the Chinese elderly 163 that short sleep duration was associated with high rates of depressive symptoms. This result was consistent with the results of Wen et al (2019), who found that elderly people with long sleep duration at night have a lower risk of developing depressive symptoms than those with short sleep duration. Sleep and depressive symptoms have a multifaceted interplay between them.…”
Section: Sleep Durationsupporting
confidence: 93%
“…A recent systematic review and meta-analysis [41] that included eight studies carried out in Spain reported an 11% overall prevalence for the over-65 population. As for depression, a recent prevalence study [7] among middle-aged and older adults revealed that, after a four-year follow-up, overall incidence was 22.3%, with much higher percentages in rural areas (25.7%) and among women (27.9%). Compared with individuals who described their health status as poor, those who reported excellent health were 62% less likely to develop depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenia has been associated with multiple adverse physical effects (e.g., alterations in movement patterns, loss of independence and the need for long-term care [6]) and psychological effects, most commonly anxiety and depression. The prevalence of depression among the older population worldwide is around 7% and increases with age [7]. The incidence of anxiety in people over 60 is between 0.7 and 18.6%, with lower frequency among the elderly than in younger adults [8].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were asked whether they suffered from a range of 15 commonly observed conditions among the elderly, including high blood pressure, diabetes, liver disease, etc., and participants chose from “0” (no) or “1” (yes). This measure was adapted from the China Health and Retirement Longitudinal Study (CHARLS) ( 20 , 21 ). A composite score of physical illness was calculated by adding the responses from the 15 items, ranging from 0 to 15, with a higher score indicating poorer physical health.…”
Section: Methodsmentioning
confidence: 99%